The Use of Noninvasive Positive Pressure Ventilation following Pediatric Tonsillectomy. (August 2017) - Buzi, Adva; Coblens, Orly M.; MacGillivray, Michael; Elden, Lisa
Objective: To determine the risks of bleeding and other complications in pediatric patients who require noninvasive positive pressure ventilation (PPV) in the immediate posttonsillectomy period. Study Design: Case series with chart review. Setting: Single tertiary pediatric hospital. Subjects and Methods: Sixty-nine patients who had undergone tonsillectomy from July 2007 through December 2013 and required postoperative PPV were reviewed. Data collected included age, sex, medical history, preoperative polysomnogram parameters, length of use and type of noninvasive ventilatory support, and postoperative complications. Bleeding rate was calculated. Results: Sixty-nine children met inclusion criteria for the study. Most had comorbid conditions. The mean age of these patients was 6.4 years. The postoperative bleeding rate of children who required operative intervention for control was 5.97%. Patients did not experience other complications. Conclusion: This is the largest study in the literature investigating bleeding in pediatric patients undergoing tonsillectomy who required postoperative noninvasive PPV. Some hesitation may exist in using this form of ventilation when open pharyngeal wounds are exposed to pressure, but this study suggests that it can be used as a suitable alternative to invasive ventilation.